Major emerging alien plants in Austrian crop fields. (17th October 2017) - Follak, S; Schleicher, C; Schwarz, M; Essl, F
Summary: Globalisation and increasing trade have led to the introduction of alien plants that are highly competitive and difficult to control in agriculture in central Europe. Our study set out to analyse the invasion process and agricultural impact of the six emerging alien plants Abutilon theophrasti, Ambrosia artemisiifolia, Cyperus esculentus, Datura stramonium, Panicum schinzii and Sorghum halepense in Austria, based on a large distribution data set (694 occurrence records in crop fields). We found that all study species have increased in abundance and range, especially after the year 2000. The rate of spread was highest for A. artemisiifolia and lowest for C. esculentus . At present, records of the study species were largely associated with areas of high summer crop concentration in eastern, southern and north‐western Austria. Based on the CORINE land‐cover data set, we found that the agricultural area at risk of being invaded increased over time. At present, it ranges between 45 500 and 168 000 ha (approximately 2.4% and 8.7% of the total agricultural area) depending on the species. The invasion success of the study species is probably associated with frequent human‐mediated dispersal, specific crop‐dominated rotations and herbicide use. Our results suggest that the study species will successfully spread further. We conclude that these emerging alien species will cause substantial impacts on crops in Austria and probably in other countries of central Europe.